Leukemic phase of anaplastic lymphoma kinase positive, anaplastic large cell lymphoma - Vijaya S Gadage; P G Subramanian; Komal S Galani; Kunal K Sehgal; Sachin P Johari; Vijay S Ghogale; Y Badrinath; K Ashok; Sumeet Gujral (Wolters Kluwer Medknow Publications, 2011)
Anaplastic large cell lymphoma (ALCL) is a distinct type of CD30+ T/null-cell non-Hodgkin's lymphoma that frequently involves nodal and extranodal sites. The presence of leukemic phase in ALCL is extremely rare and occurs exclusively with ALK1-positive ALCL. We describe two patients with ALK1-positive ALCL who developed a leukemic phase with rapid progression of the disease. Immunophenotypic pattern assessed on peripheral blood by flow cytometry revealed CD45, CD30, and CD25 positivity in both cases but NPM-ALK1 was expressed in only one case. Both patients developed leukemic phase as a terminal event of the disease and we share the immunophenotypic features of both cases.